Proof-of-concept study on a wave energy converter based on the roll oscillations of multipurpose offshore floating platforms - Daniel Clemente (2020)
Inspired by observing the motions of vessels at sea, the E-Motions has been proposed as an innovative concept capable of converting wave (and wind) induced roll oscillations on multipurpose offshore floating platforms into electricity. The device can be integrated, theoretically, into any type of offshore floating structure, given its simple 3-component design: floating platform, encasing and sliding Power Take-Off. This latter component can be sheltered from the marine environment by being placed within a casing, at deck level, or the hull of the offshore structure. With so much potential for application at sea, it was important to subject the E-Motions to an initial proof-of-concept, as done for other wave energy converters. This paper presents and discusses the main results and conclusions of an experimental study, carried out with a 1:40 reduced scale physical model, aimed at demonstrating the technical and technological viability of the E-Motions. It was found that, for the considered study variables, the device can operate without major incident and convert electricity from wave induced roll oscillations. Four ballast configurations were considered, of which two yielded higher power outputs. The average measured power reached as high as 11 kW and 13 kW, respectively, with the values reducing for wave period further away from the resonance range and lower wave heights. Power Take-Off damping was found to be an important variable that can considerably influence the energy generation process, yet it will be imperative to further assess this variable in combination with other pertinent variables, such as an external attached mass and different generators. This is key to better understand and describe the complex and non-linear relationship between the motions of the Power Take-Off and the floating platform components.